Kaedah dimetilmetilena biru (DMB) dan elektroforesis resolusi tinggi (ERT) dalam pendiagnosaan mukopolisakaridosis (MPS) - Saruddin, Abbas (2008)
The absent of a referral centre for mucopolysaccharidosis (MPS) in Malaysia is a major problem in detecting cases of these genetic disorders. As a move towards the betterment in health care system, development and optimization of the two proposed methods in this study were done for the diagnosis of MPS. One of the two methods was measuring the amount of total glycoaminoglycans (GAG) excreted by dimethylmethylene blue (DMB) method and the other was characterization of the total GAG by high resolution electrophoresis (HRE). Both methods were chosen based on literature reviews and reports of their superiority compared to the other available methods. By using these two methods the prevalence percentage of MPS and the agreement between both methods were obtained. 79 randomized urine samples from the year 1998 to 2006 were obtained from children suspected of MPS based on their clinical presentations from Universiti Sains Malaysia Hospital (HUSM), were used in this study. These samples which were kept at ( -70°C) during the years were analyzed together with 28 randomized urine samples from normal children. Results based on the DMB method revealed abnormal findings of 70% in the samples analyzed. This method cast doubts in giving falsely positive results as the analysis on the normal urine samples also exhibit 57% abnormality (falsely high). However the HRE method gave a much more convincing result as only 4% of the samples analyzed showed abnormal bands and no false positive result was given by this method. The prevalence percentage obtained in this study based on DMB method was 70 % and the HRE method was 4%. However based on 100% specificity given by ERT, we concluded that the prevalence percentage of MPS cases in HUSM was 4 %. Method agreement between both was poor based on Kappa coefficient, k was only 0.034. Combination of both methods in this study however was found to have potential in eliminating false positive results.